Potenziale und Herausforderungen des Digital Selling im B2B-Kaufentscheidungsprozess: Identifikation verschiedener Vertriebsrollen unter Berücksichtigung der Zwei-System-Theorie von Kahneman - Tanja Zweigle; Jacqueline Heinl (IU Internationale Hochschule, 2023)
– The change in customer behaviour in B2B markets associated with digitization requires an adaptation of existing sales strategies and leads to major challenges regarding the influence on the customer during the purchase decision process, especially for small and medium-sized B2B companies. Based on Kahneman's dual-process-theory and Kotler's purchase decision process, it is shown to what extent the emotional and intuitive system and the rational and consciously acting system are involved in the phases of the purchase decision process. Based on these theoretical findings and the qualitative expert interviews, several decision-making factors, used by the customers during these phases, as well as the possibilities of influencing the purchase decision in the context of digital selling are highlighted. With help of the grounded theory, correlations between the phases of the purchase decision process, the customer's decision-making behaviour and the applied sales strategy became obvious whereby different sales roles could be identified. These sales roles are associated with different potentials and challenges in influencing the customer. At the same time,they make it clearthat the customer should always be addressed on a rational and emotional level and that a balance must be found between digital sales and personal contact in order to influence the customer's decision-making behaviour.
Keywords: M31; 650; Digital Selling; B2B-Vertrieb; Digital Sales Strategy; Dual-Process-Theory